La transdisciplinarité pour une géographie décloisonnée - Anthony Tchékémian (Études Caribéennes)
This article is the result of a scientific introspection based on the observation of my studies and my career path, between studies in the environment, planning and urban development, leading to a reflection on geography as a university discipline, at the heart of my profession as a teacher-researcher. The first part presents planning as a discipline that aims to distribute and order the components of a territory, with a view to the future. The second defines urban planning as a practice at the crossroads of engineering, architecture, art and geography’s sister disciplines, economics, sociology and law. A third argues for the importance of transdisciplinarity in favour of a decompartmentalized geography. Finally, the hybridization of science and popularization leads to a conclusion on the evolution of the profession, highlighting the advantages and pitfalls for society.